Nano-CMOS and post-CMOS electronics. - Mohanty, Saraju P.; Srivastava, Ashok (College teacher) (The Institution of Engineering and Technology, 2016)
Over two volumes this work describes the modelling, design, and implementation of nano-scaled CMOS electronics, and the new generation of post-CMOS devices, at both the device and circuit levels.
Keywords: Metal oxide semiconductors, Complementary -- Design and construction.; elektronické knihy; electronic books